Differential sensitivity to speech rhythms in young and older adults - Pearson, Dylan V.; Shen, Yi; McAuley, J. Devin; Kidd, Gary R. (Frontiers in Psychology, 2023)
Sensitivity to the temporal properties of auditory patterns tends to be poorer in older listeners, and this has been hypothesized to be one factor contributing to their poorer speech understanding. This study examined sensitivity to speech rhythms in young and older normal-hearing subjects, using a task designed to measure the effect of speech rhythmic context on the detection of changes in the timing of word onsets in spoken sentences. A temporal-shift detection paradigm was used in which listeners were presented with an intact sentence followed by two versions of the sentence in which a portion of speech was replaced with a silent gap: one with correct gap timing (the same duration as the missing speech) and one with altered gap timing (longer or shorter than the duration of the missing speech), resulting in an early or late resumption of the sentence after the gap. The sentences were presented with either an intact rhythm or an altered rhythm preceding the silent gap. Listeners judged which sentence had the altered gap timing, and thresholds for the detection of deviations from the correct timing were calculated separately for shortened and lengthened gaps. Both young and older listeners demonstrated lower thresholds in the intact rhythm condition than in the altered rhythm conditions. However, shortened gaps led to lower thresholds than lengthened gaps for the young listeners, while older listeners were not sensitive to the direction of the change in timing. These results show that both young and older listeners rely on speech rhythms to generate temporal expectancies for upcoming speech events. However, the absence of lower thresholds for shortened gaps among the older listeners indicates a change in speech-timing expectancies with age. A further examination of individual differences within the older group revealed that those with better rhythm-discrimination abilities (from a separate study) tended to show the same heightened sensitivity to early events observed with the young listeners.